Proyecto de inversión para la producción de aceites corporales con aloe vera para niños - Tutiven Rodriguez, Edgar (2009)
The first part of this work is an investigation of other oil products that already exist in the market through Internet, books and magazines, where we can obtain important knowledge about producing and commercializing the Aloe Vera Oil. The second part is related to performing public opinion poll, which is the most appropriate strategy to obtain descriptive information. The main advantage of a research through opinion poll is it flexibility. You can obtain different type of information in diverse market scenarios. The tools to be used for the financial analysis of the proposed marketing plan are TIR, VAN and the sensibility and Point of equilibrium analysis. These tools will proof the profitability of the project which includes new market strategies that requires an increase in some expenses such as publicity and some changes in the final product, if necessary. However, there is also an expected reduction of costs while optimizing and improving the functions actually performed by the company. The project will take place at “La Bajada”, a little town close to the Colonche Village in Santa Elena County, where already exist 20 Has. of sabila plantation.